Feast : humans share food - "Jones, Martin" (New York, 2007)
Is sharing food such an everyday, unremarkable occurrence? In fact, the human tendency to sit together peacefully over food is actually rather an extraordinary phenomenon, and one which many species find impossible. It is also a pheonomenon with far-reaching consequences for the global environment and human social evolution. So how did this strange and powerful behaviour come about? In Feast, Martin Jones uses the latest archaeological methods to illuminate how humans came to share food in the first place and how the human meal has developed since then. From the earliest evidence of human consumption around half a million years ago to the era of the TV dinner and the drive-through diner, this fascinating account unfolds the history of the human meal and its huge impact both on human society and the ecology of the planet.
Keywords: Social psychology